Mechanical, tribological and electrochemical corrosion properties of in-situ synthesized Al2O3/TiAl composites. (May 2020) - Lu, Xiaofang; Li, Jianbo; Chen, Xianhua; Qiu, Jingwen; Wang, Yan; Liu, Bin; Liu, Yong; Rashad, Muhammad; Pan, Fusheng
Abstract: TiAl-based composites reinforced with different weight fractions of Al2 O3 have been successfully synthesized by hot-pressing using the pre-alloyed Ti–45Al–7Nb-0.2B and Nb2 O5 powders. The microstructures, mechanical and tribological properties of composites were examined. The as-sintered TiAl composites mainly consist of γ-TiAl phase, α2 -Ti3 Al phase, γ/α2 lamellar colony, TiB2 particles and Al2 O3 particles. The microstructure can be refined by synthesizing Al2 O3 particles. The volume fractions of α2 phase and α2 /γ lamellar colonies increased with the increasing of Al2 O3 content. When the Al2 O3 content increases to 0.5 wt %, the composite exhibited the best comprehensive mechanical properties with the yield stress of 1032 ± 13 MPa and fracture strength of 2668 ± 15 MPa. For the Al2 O3 /TiAl composites, the fracture type is mainly composed of transgranular, translamellar and delamination fracture. The friction coefficient of 0.5 wt % Al2 O3 /TiAl composite is lower than other TiAl composites due to its homogeneous distribution of Al2 O3 particles. The main wear mechanism of Al2 O3 /TiAl composites was determined to be abrasive wear along with plowing grooves. Addition of Al2 O3 particles can improve the corrosion resistance of TiAl composites. Highlights: The fractions of α2 phase and α2 /γ lamellar colonies increase with the content of Al2 O3 increasing. The 0.5 wt% Al2 O3 /TiAl composite exhibits the best comprehensive mechanical properties. The wear mechanism of Al2 O3 /TiAl composites was abrasive wear companied by plowing grooves.